Marzouqi, Abu Yaʿrub. “Vicegerent Spirituality: Characteristics and Conditions,” Year 4, Issue 13 (Summer 1419 AH/ 1998 CE), Pp. 67-106. - المرزوقي أبويعرب (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 1998)
Abu Yaʿrub Marzouqi’s article discusses what he deems to be the illusion that there is a separation between spiritual and psychological aspects in human life and mental and scientific aspects. He goes on to analyze the dimensions of mental, scientific, spiritual, and value-based human experience by critiquing the inward and incarnation-based (ḥulūlī) philosophical tendencies. He emphasizes that Qur’anic revelation was sent as the basis for human life, which derives its strength from interdependence and integration between these elements and dimensions, with a focus on the foundation of tawḥīd (pure monotheism) and human vicegerency (istikhlāf) on earth. He outlines the obstacles in the way of realization of spirituality and vicegerency and their principles; and he addresses the science of vicegerency-based tawḥīd (al-tawḥīd al-istikhlāfī), the phases of the human spiritual experience, and the stages that achieved the essence of the messages of the Prophet Muhammad, the Prophet Moses, and the Prophet Jesus, and the existential evidence and targeted values.